SYNTHESIS, CHARACTERIZATION AND RAPID ADSORPTIVE REMOVAL OF BASIC RED 46 DYE USING MAGNETIC FE₃O₄@CNT COMPOSITE - Salman, Meriç Yılmaz (My University, 2026)
The rapid pollution of water resources continues to increase, particularly due to the spread of synthetic dyes from the textile industry into aquatic environments. The increasing use of toxic and poorly biodegradable compounds, such as azo dyes, poses serious risks to both ecosystem health and human health. Therefore, the need for cost-effective, fast, and efficient adsorbents is growing. In this study, a magnetic carbon nanotube composite (Fe3O4@CNT) was synthesized and its adsorption performance evaluated for the removal of Basic Red 46 (BR 46) dye from water. Fe3O4 nanoparticles were prepared using a solvothermal method and combined with CNTs to form a composite structure. FTIR, SEM-EDX, and XRD analyses showed that the composite was successfully synthesized and maintained its structural integrity after adsorption. Batch adsorption experiments were carried out to investigate the effects of contact time, initial dye concentration, adsorbent dosage, solution pH, and temperature on the adsorption performance of Fe3O4@CNT toward BR46 dye. The composite exhibited rapid kinetic behavior, achieving approximately 95% removal in just 15 minutes. In kinetic analyses, the pseudo second order model showed the best fit, while in isotherm analyses, the Langmuir model was dominant. The maximum adsorption capacity was calculated to be approximately 47 mg/g.
Keywords: Nanobilim ve Nanoteknoloji; Çevre Mühendisliği; Malzeme Bilimleri; Kompozitler